Paradigm and Perspective Changes in Indian Forestry - Misra, A. P.; Verma, A. K. (Indian Forester, 1999)
The pattern of Forest Management in India and perspective changes with technology, organizational model, institutional frame work and consequential effects have been discussed for sustainable management of the forests.